Narrativas cartográficas: espaço e literatura de autoria feminina na América Latina - Isadora Carraro Tavares Monteiro (2019)
Cartographic Narratives proposes the reading of the literary works of Latin American women as cartographic devices, potential platforms for the production of spatial knowledge. Having as a starting point the perception that the narrative is a spatial practice, the research pursuits a new way of looking at the territory and the landscape through the lenses of women's stories, in an effort to bring to the center of the discussion voices historically silenced in the processes of the production of space. Based on the theoretical background of the decolonial and feminist studies, the thesis focuses on women’s literature as a potent instrument for the creation of gendered epistemologies of the south, that is, epistemologies that challenge the colonizing hegemonic narratives and that understand the gender specificities as fundamental for the construction of other kinds knowledges. In this sense, the research proposes readings (or sensitive listening) of some Latin American authors, linking their writing to a space type, from where their discourses are born and expand. The first of these authors is Carolina Maria de Jesus, a Brazilian writer who published, in 1960, the book Quarto de Despejo, a paradigmatic work of the so-called marginal literature, which reports the space of the favela and the trajectories of black woman in the city of São Paulo; after, the dialogue advances to the Madres de Plaza de Mayo, a group of women who, since 1977, meet and march in the downtown square of Buenos Aires to protest the lives of their children, killed by the Argentinian military dictatorship, and that, in the decade of 1990, published the book of poems El Corazón en la Escritura, written collectively by the mothers during literature workshops; the third author is Valeria Luiselli, a young Mexican writer who, instigated by the United States immigration crisis, started in 2014, publishes the essay Tell Me How It Ends and the novel Lost Children Archive, mapping the border and the trajectories of children and adolescents, from Central America to US immigration courts. Cartographic Narratives also seeks to associate to each of the readings, contemporary practices in the arts and in the social movements, in which the concepts and reflections initiated by the authors, in their works and different places of enunciation, appear adapted and expanded through other experiences and pedagogies.